2017
DOI: 10.5628/rpcd.17.s1a.90
|View full text |Cite
|
Sign up to set email alerts
|

Efeito da idade relativa nos jogadores do campeonato brasileiro de basquete da categoria sub-17

Abstract: Efeito da idade relativa nos jogadores do campeonato brasileiro de basquete da categoria sub-17 PALAVRAS CHAVE: Idade Cronológica. Efeito da idade relativa. Desempenho Desportivo. Basquetebol. RESUMO O objetivo do estudo foi verificar o efeito da idade relativa (EIR) nos jogadores do campeonato brasileiro de basquete sub-17, considerando o sexo e a classificação das equipes. Assim, foi identificado o trimestre de nascimento (quartis) de 540 basquetebolistas (270 de cada sexo). Para compara-los pela classifica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 15 publications
2
3
0
Order By: Relevance
“…In the present study, for example, RAE was not associated with the performance of men's teams, but it was observed that RAE could somehow influence the results for females, since this phenomenon was found only in athletes from the best classified teams. Similar result was found in U-17 Brazilian basketball players 18 . The association of RAE with the final classification of the team found in this study and in the study of Oliveira et al 18 suggest as a consequence of RAE in the Brazilian Women's Championship a better performance of teams in the U-15 and U-17 categories.…”
Section: Discussionsupporting
confidence: 78%
See 4 more Smart Citations
“…In the present study, for example, RAE was not associated with the performance of men's teams, but it was observed that RAE could somehow influence the results for females, since this phenomenon was found only in athletes from the best classified teams. Similar result was found in U-17 Brazilian basketball players 18 . The association of RAE with the final classification of the team found in this study and in the study of Oliveira et al 18 suggest as a consequence of RAE in the Brazilian Women's Championship a better performance of teams in the U-15 and U-17 categories.…”
Section: Discussionsupporting
confidence: 78%
“…Similar result was found in U-17 Brazilian basketball players 18 . The association of RAE with the final classification of the team found in this study and in the study of Oliveira et al 18 suggest as a consequence of RAE in the Brazilian Women's Championship a better performance of teams in the U-15 and U-17 categories. However, the same cannot be said about the final classification of men's teams.…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations